Advance in Drug Resistance Mechanism of Immune Checkpoint Inhibitors - ZHANG Lanlan; LI Xiangmin; FAN Zaiwen (Zhongliu Fangzhi Yanjiu, 2020)
At present, immune-therapy, especially immune checkpoint inhibitors(ICI) therapy, has become a hot topic in cancer research field. With the wide application of ICI in the field of cancer, some patients benefit from ICI, some patients appeared disease progression or recurrence after effective treatment for a period of time and some patients did not respond to ICI in the first place. The resistance to ICI can be classified into primary, adaptive and acquired resistance. This article will review those resistance mechanisms of ICI therapy.